CONTENT-PROCESS APPROACH IN PROJECTING PROFESSIONALISM OF A MODERN TEACHER - Kondrashova, L.V. (Pedagogy of Higher and Secondary Education, 2010)
The article reveals the essence, the main haracteristics of content-proceural approach in learning and its possibilities in the professional formation of futre teachers in university education.